Environment-friendly anticorrosive paint for aluminum alloy parts
By using arginine modified sulfonated carbon nanotubes, zirconium phosphate nanosheets and spherical zinc powder in aqueous coatings, the problem of insufficient corrosion resistance caused by carbon nanotube agglomeration is solved, and efficient corrosion and fire resistance is achieved, and service life is extended.
Patent Information
- Application Number
- CN202510014478.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-06
- Publication Date
- 2025-04-11
- Estimated Expiration
- 2045-01-06
AI Technical Summary
Carbon nanotubes are prone to agglomeration in water-based coating systems, resulting in insufficient anti-corrosion performance of water-based coatings.
Arginine-modified sulfonated carbon nanotubes are used, combined with zirconium phosphate nanosheets and spherical zinc powder, and grinding and stirring to form an efficient anticorrosion coating.
It significantly improves the corrosion and fire resistance of anti-corrosion coatings, has good weather resistance, long service life, and the introduction of carbon nanotubes improves the conductive and anti-corrosion properties of the coating.
Smart Images

Figure CN119799105A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of coatings, and in particular to an environmentally friendly anti-corrosion coating for aluminum alloy parts. Background Art
[0002] Nanomaterials have been widely used in the field of anti-corrosion and fire protection technology due to their unique physical and chemical properties. Nanomaterials have a high surface area and high surface energy, which allows them to form a dense protective layer on the surface of the material, thereby effectively preventing the penetration of corrosive media. In addition, nanomaterials have good dispersibility in coatings and can form a strong bond with the substrate, significantly improving the durability and protective properties of the coating.
[0003] Carbon nanotubes (CNTs) have shown significant advantages in the field of corrosion protection due to their excellent mechanical strength, electrical conductivity and chemical stability. CNTs can form a network structure in the coating to enhance the mechanical properties and durability of the coating. In addition, the high electrical conductivity of CNTs helps to improve the antistatic and anti-corrosion properties of the coating. However, CNTs are prone to agglomeration in the coating system and have poor dispersion in the coating system, which significantly affects the effective performance of their performance.
[0004] Arginine is an amino acid compound with a high concentration of nitrogen atoms and amine groups. It has the potential to become a VCI vapor corrosion inhibitor. Since pure arginine molecules are amino acid substances, they are easily deteriorated in the atmospheric environment. Therefore, the use of arginine derivatives is expected to become VCI vapor corrosion inhibitors and be used in the field of corrosion protection. Summary of the invention
[0005] The problem in the prior art is that carbon nanotubes are prone to agglomeration in the water-based coating system, and the anti-corrosion performance of the obtained water-based coating needs to be further improved. In view of the above problems, the present invention provides an environmentally friendly anti-corrosion coating for aluminum alloy parts, which includes the following components by mass ratio:
[0006]
[0007] Preferably, an environmentally friendly anti-corrosion coating for aluminum alloy parts comprises the following components by mass ratio:
[0008] Water-based latex 20%;
[0009] Arginine modified sulfonated carbon nanotubes 20-30%;
[0010] Zirconium phosphate nanosheets 10-30%;
[0011] Spherical zinc powder 20%;
[0012] Hydroxyethylcellulose 0.5-1%;
[0013] Ethylene glycol methyl ether 1%;
[0014] Propylene glycol butyl ether 0.5%;
[0015] Dispersant 0.5%;
[0016] Defoaming agent 0.5%;
[0017] n-Octanol 0.5%;
[0018] Water 15-18%.
[0019] Preferably, the solid content of the aqueous latex is 30-55%, and the coagulation rate is 0.1-2%.
[0020] Preferably, the aqueous latex comprises aqueous acrylate emulsion, aqueous methacrylate emulsion, aqueous styrene acrylic emulsion or aqueous styrene acrylic core-shell emulsion.
[0021] Preferably, the preparation method of the arginine-modified sulfonated carbon nanotubes is as follows:
[0022] Arginine and sulfonated carbon nanotubes are added to a mixed solution formed by ethanol and water in a volume ratio of 50-100:100-50 in a mass ratio of 50-100:50-100, wherein the mass concentration of arginine in the mixed solution is 10wt%-50wt%, and ultrasonic reaction is carried out at 50-100°C for 12-48h. Subsequently, a DC5700 solution is added to the reaction system, and ultrasonic reaction is carried out at 50-100°C for 12-48h. After the reaction is completed, the obtained reaction solution is subjected to solid-liquid separation, and the obtained solid product is washed with tetrahydrofuran and then dried to obtain arginine-modified sulfonated carbon nanotubes, wherein the mass ratio of the DC5700 solution to the arginine added to the reaction system is 50-100:50-100.
[0023] Preferably, the average particle size of the sulfonated carbon nanotubes is 10-20 nm, and the length is 500-1000 nm.
[0024] Preferably, the DC5700 solution is prepared by dissolving octadecyldimethylsilylammonium chloride in anhydrous methanol, with a mass concentration of 40-60 wt %.
[0025] Preferably, the average particle size of the zirconium phosphate nanosheets is 100-300 nm, and the diameter is 1000-1500 nm.
[0026] Preferably, the preparation method of the environmentally friendly anti-corrosion coating for aluminum alloy parts comprises the following steps:
[0027] (1) according to the formula, arginine-modified sulfonated carbon nanotubes, zirconium phosphate nanosheets, spherical zinc powder, and hydroxyethyl cellulose are uniformly mixed and ground into a powder without particles, and then water is added and stirred and ground until uniform without obvious particles, and then a defoamer and a dispersant are added, and stirring and grinding is continued to be uniform;
[0028] (2) Finally, the remaining amount of raw materials is added to the reaction system obtained in step (1), and the mixture is ground and mixed evenly to obtain the product. The present invention has the following beneficial effects:
[0029] (1) The anticorrosive coating obtained by the present invention has good anticorrosion and fireproof properties, good weather resistance and long service life;
[0030] (2) Compared with the traditional vapor phase corrosion inhibitor, the arginine-modified sulfonated carbon nanotubes added to the anti-corrosion coating of the present invention can anchor and adsorb arginine, and can slowly release amine small molecules into the atmosphere, thereby improving the anti-corrosion performance and extending the corrosion resistance time. In addition, the introduction of carbon nanotubes also helps to improve the conductivity of the coating and reduce its impedance, and the synergistic effect further improves the anti-corrosion performance of the coating;
[0031] (3) The introduction of two-dimensional nano zirconium phosphate sheets into the coating system can further enhance the anti-corrosion effect of the coating through the covering effect. The two-dimensional nano zirconium phosphate and one-dimensional carbon nanotubes work together to build an anti-corrosion covering network, which helps to further reduce the release of small amine molecules into the air, thereby further improving the anti-corrosion performance of the coating. BRIEF DESCRIPTION OF THE DRAWINGS
[0032] Figure 1 : Nyquist spectra of the coatings obtained in Example 1 and Comparative Example 3 after being immersed in a 3.5% NaCl aqueous solution for 7 days.
[0033] Figure 2 : are Bode spectra of the coatings obtained in Example 1 and Comparative Example 3 after being immersed in a 3.5% NaCl aqueous solution for 7 days.
[0034] Figure 3 : It is the surface microscopic morphology of Example 1 (a in the figure) and Comparative Example 3 (b in the figure) after salt spray corrosion test. DETAILED DESCRIPTION
[0035] The present invention is described in detail below with reference to the examples. However, it should be understood that the following examples are only illustrative of the embodiments of the present invention, and are not intended to limit the scope of the present invention.
[0036] The sulfonated carbon nanotubes in the following examples of the present invention have an average particle size of 20 nm and a length of 500 nm, and are purchased from Chengdu Organic Chemistry Co., Ltd., Chinese Academy of Sciences.
[0037] The zirconium phosphate nanosheets in the following examples of the present invention have an average particle size of 300 nm and a diameter of 1000 nm, and are purchased from Aladdin Reagent (Shanghai) Co., Ltd.
[0038] The spherical zinc powder in the following examples of the present invention was purchased from Guangdong Haozhisheng New Materials Co., Ltd. and had an average particle size of 5 μm.
[0039] The arginine in the following examples of the present invention is L-arginine.
[0040] The dispersant used in the following embodiments of the present invention is wetting dispersant 5040, and the defoaming agent is silicone defoaming agent 470.
[0041] The aqueous latex in the following embodiments of the present invention is an aqueous acrylate-based emulsion with a core-shell structure, and the preparation method is as follows:
[0042] (1) Dissolve 1.0 g of alkylphenol polyoxyethylene ether and 2.0 g of sodium lauryl sulfate in 90 mL of deionized water to prepare an emulsifier aqueous solution, and divide the solution into three portions of 35 mL, 30 mL, and 25 mL;
[0043] (2) adding 50 g of n-butyl acrylate and 10 g of methyl methacrylate to 35 mL of an emulsifier aqueous solution, stirring and mixing at room temperature, and pre-emulsifying for 1 hour to prepare a core pre-emulsion;
[0044] (3) adding 10 g of n-butyl acrylate, 30 g of methyl methacrylate and 2.4 g of methacrylic acid to 30 mL of an aqueous emulsifier solution, stirring and mixing at room temperature, and pre-emulsifying for 2 h to obtain a shell pre-emulsion;
[0045] (4) dissolving 0.3 g of sodium bicarbonate in 25 mL of an emulsifier aqueous solution and stirring to dissolve, thereby preparing a buffer aqueous solution; adding 0.5 g of potassium persulfate to 30 mL of deionized water and stirring to dissolve, thereby preparing an initiator aqueous solution;
[0046] (5) In a reaction container, add a buffer solution, 1 / 3 volume of an initiator solution, and 1 / 2 volume of a core pre-emulsion solution in sequence while stirring, raise the temperature to 70° C., and when a large amount of blue light appears in the emulsion, keep the temperature for 0.5 h to obtain a seed emulsion;
[0047] (3) When the seed emulsion is incubated for 0.5 h, slowly drip the remaining core pre-emulsion and 1 / 3 of the initiator aqueous solution into the seed emulsion, and complete the dripping within 1 h. Control the temperature to 80° C. and keep it incubated for 0.5 h to obtain the core layer emulsion.
[0048] (4) When the core layer emulsion is finished being kept warm, the remaining initiator aqueous solution and the formulated amount of shell pre-emulsion are added dropwise, and the dripping is completed within 1.5 hours. The temperature is then raised to 85°C and kept warm for 0.5 hours. The mixture is then naturally cooled to 40°C, the pH value is adjusted to 8, and the mixture is passed through a 200-mesh sieve to obtain an acrylate-based emulsion (core-shell structure) having a solid content of 41% and a coagulation rate of 0.34%.
[0049] The arginine-modified sulfonated carbon nanotubes in the following embodiments of the present invention are prepared as follows:
[0050] Arginine and sulfonated carbon nanotubes are added to a mixed solution formed by ethanol and water in a mass ratio of 1:1 in a mass ratio of 50:100, wherein the mass concentration of arginine in the mixed solution is 13wt%, and after being stirred and mixed evenly, the mixture is stirred and ultrasonically reacted for 12h at a temperature of 80°C, and the ultrasonic power is 200W. Subsequently, a DC5700 solution having a mass ratio of 50:64 to arginine is added, and the mixture is stirred and ultrasonically reacted for 12h at an ultrasonic power of 200W. After the reaction is completed, the mixture is centrifuged at 6000rpm, and the obtained solid product is washed with tetrahydrofuran and dried at 80°C. The DC5700 solution is prepared by dissolving octadecyldimethylsilylammonium chloride in anhydrous methanol, and its mass concentration is 60wt%.
[0051] Example 1
[0052] An environmentally friendly anti-corrosion coating for aluminum alloy parts, the composition of which is as follows by mass ratio:
[0053]
[0054]
[0055] Example 2 is the same as Example 1, except that the anticorrosive coating in Example 2 has the following components by mass ratio:
[0056]
[0057] Example 3 is the same as Example 1, except that the anticorrosive coating in Example 3 has the following components by mass ratio:
[0058]
[0059] Comparative Example 1 is the same as Example 1, except that no zirconium phosphate nanosheets are added in Comparative Example 1.
[0060] Comparative Example 2 is the same as Example 1, except that the mass fraction of spherical zinc powder added in Comparative Example 2 is 40%.
[0061] Comparative Example 3 is the same as Example 1, except that the arginine-modified carbon nanotubes in Example 1 are replaced by the arginine-modified sulfonated carbon nanotubes in Comparative Example 3 with the same amount of arginine-modified carbon nanotubes added. The arginine-modified carbon nanotubes are prepared according to the method disclosed in Example 1 of Chinese invention patent CN116082869A:
[0062] 1 part by mass of carbon nanotubes was dispersed in a mixture of 100 parts by mass of water and ethanol in a mass ratio of 10:1, and then the pH was adjusted to 1 with hydrochloric acid. Then 10 parts by mass of arginine was added to the reaction system, and refluxed at 60°C for 1 hour, filtered and dried to obtain arginine-modified carbon nanotubes.
[0063] Performance Testing
[0064] The relevant performance tests were carried out on the anti-corrosion coatings obtained in Examples 1-3 of the present invention and Comparative Examples 1-3, and the test results are shown in Table 1.
[0065] Salt spray corrosion resistance: Tested in accordance with GB / T 10125-2021 national standard. Use 5% sodium chloride solution, the salt spray temperature is 35±2℃, and the test sample is placed at an angle of 15° to 30°. The test time is 72 hours
[0066] Storage stability: Place the coating at room temperature, observe and record the time (months) it takes for the coating to begin to delaminate.
[0067] Surface morphology after salt spray corrosion resistance: Check the rust condition of the coating surface according to the requirements of GB / T 1766-2008 "Rating method for aging of paint and varnish coatings".
[0068] The evaluation criteria are as follows:
[0069] Ri0: 0% rust area, no rust.
[0070] Ri1: 0.05% rusted area, very slightly rusted.
[0071] Ri2: 0.5% rusted area, slightly rusted.
[0072] Ri3: 1% rusted area, obvious rust.
[0073] Ri4: 8% rust area, large rust.
[0074] Ri5: 40%-50% rusted area, severe rust.
[0075] The surface microscopic morphology of Example 1 (a) and Comparative Example 3 (b) after salt spray corrosion test (magnification 500 times) are shown in the attached manual. Figure 3As shown, the results show that the carbon nanotube agglomerates in Example 1 are significantly lower than those in Comparative Example 3 and are more evenly dispersed.
[0076] Table 1
[0077] Test items Paint appearance Storage stability (month) Surface morphology after corrosion Example 1 Dark grey, smooth texture >24 R0 Example 2 Dark grey, smooth texture >24 Ri1 Example 3 Dark grey, smooth texture >24 Ri1 Comparative Example 1 Black, smooth texture >24 Ri4 Comparative Example 2 Dark grey, smooth texture 18 Ri3 Comparative Example 3 Dark gray, with obvious particles on the surface 21 Ri2
[0078] The present invention conducted barrier property tests on Example 1 and Comparative Example 3, respectively. The coatings obtained in Example 1 and Comparative Example 3 were cured at room temperature to obtain coatings with a thickness of 500 μm. The coatings were immersed in a 3.5% NaCl aqueous solution for 7 days, and then electrochemical impedance spectroscopy was performed. The test results are shown in the attached specification. Figure 1 And the instruction manual Figure 2 shown.
[0079] In the Nyquist diagram, the larger the radius of the capacitive reactance arc in the high-frequency region, the better the barrier performance of the coating, corresponding to better corrosion resistance. Figure 1 As shown, the order of the size of the capacitive reactance arc radius in the high-frequency region is that Example 1 is greater than Comparative Example 3. It can be seen that the shielding performance of the coating obtained in Example 1 is better than that of Comparative Example 3.
[0080] In the Bode spectrum, the low-frequency impedance modulus (|Z|0.01Hz) in the electrochemical impedance test is a semi-quantitative indicator of the corresponding coating's ability to shield the penetration of corrosive media (water, oxygen, chloride ions, etc.). The larger the impedance modulus, the stronger the corresponding ability to shield the penetration of corrosive substances. Figure 2 As shown, the low-frequency impedance modulus of the coating obtained in Example 1 is obviously greater than that in Comparative Example 3, so it has a better shielding effect on corrosive media.
[0081] Based on the above ideal embodiments of the present invention, the relevant staff can make various changes and modifications without departing from the technical concept of the present invention through the above description. The technical scope of the present invention is not limited to the contents of the specification, and its technical scope must be determined according to the scope of the claims.
Claims
1. An environmentally friendly anti-corrosion coating for aluminum alloy parts, characterized in that: In terms of mass ratio, it includes the following ingredients: Water-based latex 20-30%; Arginine modified sulfonated carbon nanotubes 10-50%; Zirconium phosphate nanosheets 10-50%; Spherical zinc powder 10-50%; Hydroxyethylcellulose 0.5-1%; Ethylene glycol methyl ether 0.5-1%; Propylene glycol butyl ether 0.5-1%; Dispersant 0.5-1%; Defoaming agent 0.5-1%; n-Octanol 0.5-1%; Water 15-18%.
2. The environmentally friendly anti-corrosion coating for aluminum alloy parts according to claim 1, characterized in that: The solid content of the aqueous latex is 30-55%, and the coagulation rate is 0.1-2%.
3. The environmentally friendly anti-corrosion coating for aluminum alloy parts according to claim 2, characterized in that: The aqueous latex includes aqueous acrylate emulsion, aqueous methacrylate emulsion, aqueous styrene-acrylic emulsion or aqueous styrene-acrylic core-shell emulsion.
4. The environmentally friendly anti-corrosion coating for aluminum alloy parts according to claim 1, characterized in that: The preparation method of the arginine-modified sulfonated carbon nanotubes is as follows: Arginine and sulfonated carbon nanotubes are added to a mixed solution formed by ethanol and water in a volume ratio of 50-100:100-50 in a mass ratio of 50-100:50-100, wherein the mass concentration of arginine in the mixed solution is 10-50wt%, and then the mixture is stirred and ultrasonically reacted at a temperature of 50-100°C for 12-48h, and then a DC5700 solution is added to the reaction system, and then the mixture is stirred and ultrasonically reacted at a temperature of 50-100°C for 12-48h. After the reaction is completed, the obtained reaction solution is subjected to solid-liquid separation, and the obtained solid product is washed with tetrahydrofuran and then dried to obtain arginine-modified sulfonated carbon nanotubes, wherein the mass ratio of the DC5700 solution to the arginine added to the reaction system is 50-100:50-100.
5. The environmentally friendly anti-corrosion coating for aluminum alloy parts according to claim 4, characterized in that: The average particle size of the sulfonated carbon nanotubes is 10-20 nm, and the length is 500-1000 nm.
6. The environmentally friendly anti-corrosion coating for aluminum alloy parts according to claim 4, characterized in that: The DC5700 solution is prepared by dissolving octadecyldimethylsilylammonium chloride in anhydrous methanol, with a mass concentration of 40-60 wt %.
7. The environmentally friendly anti-corrosion coating for aluminum alloy parts according to claim 1, characterized in that: The average particle size of the zirconium phosphate nanosheets is 100-300 nm, and the diameter is 1000-1500 nm.
8. An environmentally friendly anti-corrosion coating for aluminum alloy parts according to any one of claims 1 to 7, characterized in that: The preparation method comprises the following steps: (1) according to the formula, arginine-modified sulfonated carbon nanotubes, zirconium phosphate nanosheets, spherical zinc powder, and hydroxyethyl cellulose are uniformly mixed and ground into a powder without particles, and then water is added and stirred and ground until uniform without obvious particles, and then a defoamer and a dispersant are added, and stirring and grinding is continued to be uniform; (2) Finally, the remaining amount of raw materials is added to the reaction system obtained in step (1), and the mixture is ground and mixed evenly to obtain the product.
Citation Information
Patent Citations
Carbon nano inorganic silicate anticorrosive paint
CN116082869A
CNT (carbon nano tube) polyamino acid water-soluble derivative as well as preparation method and application thereof
CN109679091A
Aqueous anticorrosive coating based on carbon nano composite material and preparation method thereof
CN110003774A
Polyether-ether-ketone composite material and preparation method thereof
CN116903991A
Metal plate coating with high wear resistance, corrosion resistance and weather resistance as well as preparation method and application of metal plate coating
CN118852928A
Cited By
Protective coating for wind power aluminum frame and preparation method of protective coating
CN120290053A